2019
DOI: 10.1055/a-0962-9780
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical resections for benign colon polyps: a systematic review

Abstract: Background Not all benign colonic polyps are suitable for endoscopic resection, although criteria for endoscopic non-resectability vary worldwide. Clinical decision-making largely depends on endoscopic treatment options, as well as postoperative risks after surgical resection. This systematic review aimed to determine postoperative outcomes and the characteristics of surgically resected benign colonic polyps. Methods MEDLINE, EMBASE, and the Cochrane Library were searched for studies investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 56 publications
2
35
0
2
Order By: Relevance
“…This suggests that most NICE Type 2 lesions and JNET Type 2A lesions might be non‐invasive, irrespective of the use of magnification. A recent systematic review demonstrated that one‐third of surgical resections of benign tumors are indicated by fear of submucosal invasion 25 . As our recent study revealed that preoperative characterization could reduce redundant surgery for benign leisons, 26 JNET type 2A classification can be a good marker for non‐invasive lesions, similar to NICE Type 2 without magnified endoscopy.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that most NICE Type 2 lesions and JNET Type 2A lesions might be non‐invasive, irrespective of the use of magnification. A recent systematic review demonstrated that one‐third of surgical resections of benign tumors are indicated by fear of submucosal invasion 25 . As our recent study revealed that preoperative characterization could reduce redundant surgery for benign leisons, 26 JNET type 2A classification can be a good marker for non‐invasive lesions, similar to NICE Type 2 without magnified endoscopy.…”
Section: Discussionmentioning
confidence: 81%
“…An AE following the treatment of a large sessile polyp is attributed either to endoscopy or to surgery depending on the type of resection. Surgical resection-related morbidity-mortality is significantly higher than endoscopic polypectomy-related morbidity-mortality [26,27]. Consequently, if the rate of referral for surgery for benign polyps is high, the individual endoscopist's or CRC screening program's colonoscopy-related AE rate will be low while the overall AE rate will be high.…”
Section: Screeningmentioning
confidence: 99%
“…Furthermore, despite the higher morbidity-mortality rate of surgical resection, when the first-line endoscopists could not remove benign LPs themselves, they referred patients to a surgeon twice as often as to a more experienced endoscopist (8,14). This led to a non-negligible volume of surgeries for benign LPs, avoidable in 32% to 74% of cases if patients had been referred to expert endoscopists (13,14,21). Surgery was definitely unwarranted in more than 60% of our benign LP patients who were As previously reported, the risk of malignancy was three-fold and two-fold higher for LPs located in the rectum and sigmoid respectively compared with the rest of the colon (31,32).…”
Section: Colonoscopies and Polypsmentioning
confidence: 99%
“…In the US, they represented 25% of surgeries for colorectal neoplasia (13). Yet, the pooled 1-month complication and mortality rates of surgery for benign polyps are 24% and 0.7%, respectively, significantly higher than those of ER (perforation 1.5%, bleeding 6.5%, mortality 0.08%) (8,14). There Our aim was to analyze presentation, management and outcomes of colorectal LPs detected in the French CRC FIT screening program.…”
Section: Introductionmentioning
confidence: 99%